Consumer attitudes and behaviour towards online shopping : exploratory study - Kwan, Yen Ling (2008)
The research seeks to explore the consumer attitudes and behaviours towards online shopping in Singapore. A random sample was drawn and analysed. Recommendations were given to the government and potential businesses venturing into e-commerce. Recommendations for future research were also contributed.